2008
DOI: 10.1002/mds.21761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Unified Wilson's Disease Rating Scale (UWDRS) in German patients with treated Wilson's disease

Abstract: Wilson's disease (WD) is an inherited autosomal-recessive disorder of copper metabolism characterized by a wide variety of neurological, hepatic, and psychiatric symptoms. The aim of the present study was the development and evaluation of a clinical rating scale, termed Unified Wilson's Disease Rating Scale (UWDRS), to assess the whole spectrum of clinical symptoms in WD. Altogether 107 patients (mean age 37.6 +/- 11.9 years; 46 male, 61 female) with treated WD participated in the study. Cronbach's alpha as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 27 publications
(31 reference statements)
2
74
0
1
Order By: Relevance
“…The results with respect to tiapride (as monotherapy, n = 3) are inconclusive since hyperkinesia is not a typical symptom in treated WD and was therefore not specifically addressed in the current study [7]. However, it is worth mentioning that tetrabenazine (in combination therapy) had a good effect on hyperkinesia in 1 patient.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The results with respect to tiapride (as monotherapy, n = 3) are inconclusive since hyperkinesia is not a typical symptom in treated WD and was therefore not specifically addressed in the current study [7]. However, it is worth mentioning that tetrabenazine (in combination therapy) had a good effect on hyperkinesia in 1 patient.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous report we already suggested that a substantial proportion of WD patients still features residual neurological symptoms [7]. Furthermore, almost half of the patients taking part in the mailed questionnaire survey subjectively reported residual neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity of neurological impairment may be scored using Unified Wilson's disease Rating Score (UWDRS) which consist 3 parts including: 1. conciousness, 2. changes in activities of daily life and 3. the results of the clinical neurological examination. 26,27 Contrary to HE, disturbed consciousness, pyramidal signs, myoclonus and/or asterixis in neurological cases of WD are very rarely observed. Another possibility to quantify the symptoms is the Global Assessment Scale (GAS) which includes global disability (tier 1: liver, cognition and behavior, motor, osseomuscular) and neurological assessment (tier 2: detailed neuropsychiatric).…”
Section: Neurological Manifestation Of Wilson Diseasementioning
confidence: 99%
“…Patients were evaluated before and after LT using both the modified Rankin scale and the more specific Unified Wilson's Disease Rating Scale (UWDRS) [6][7][8] . Items of bradykinesia, rigidity and dystonia were scored for left and right sides.…”
Section: Methodsmentioning
confidence: 99%